2005
DOI: 10.1051/0004-6361:20042189
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared luminosity as an indicator of the total infrared luminosity of galaxies

Abstract: Abstract. The infrared (IR) emission plays a crucial role in understanding the star formation in galaxies hidden by dust. We first examined four estimators of the IR luminosity of galaxies, L FIR (Helou et al. 1988 (Sanders & Mirabel 1996) by using the observed SEDs of wellknown galaxies. We found that L IR provides excellent estimates of the total IR luminosity for a variety of galaxy SEDs. The performance of L TIR2 was also found to be very good. Using L IR , we then statistically analyzed the IRAS PSCz gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 34 publications
8
97
1
Order By: Relevance
“…The discrepancy could either be explained by a larger PAH emission in distant ULIRGs or instead by the hot dust heated by a buried AGN. We note however, that part of this discrepancy could be due to uncertain local SEDs templates (Takeuchi et al 2005;Buat et al 2009). In Fig.…”
Section: Resultsmentioning
confidence: 75%
“…The discrepancy could either be explained by a larger PAH emission in distant ULIRGs or instead by the hot dust heated by a buried AGN. We note however, that part of this discrepancy could be due to uncertain local SEDs templates (Takeuchi et al 2005;Buat et al 2009). In Fig.…”
Section: Resultsmentioning
confidence: 75%
“…To check the consistency of our approach, we compared our results with those of Takeuchi et al (2005), Sajina et al (2005), Caputi et al (2007), and Bavouzet et al (2008), in particular. In their work, Caputi et al provide an empirical calibration of the conversion from νL ν (8 μm) to the bolometric IR luminosity (L IR bol ), based on a sample of Spitzer-selected galaxies, while Takeuchi et al (2005) and Sajina et al (2005) obtain a relation between νL ν (24 μm) and L IR bol .…”
Section: Total Infrared Bolometric Luminosities and Lfmentioning
confidence: 97%
“…In their work, Caputi et al provide an empirical calibration of the conversion from νL ν (8 μm) to the bolometric IR luminosity (L IR bol ), based on a sample of Spitzer-selected galaxies, while Takeuchi et al (2005) and Sajina et al (2005) obtain a relation between νL ν (24 μm) and L IR bol . Bavouzet et al (2008) elaborate on the latter by including into the analysis, data at 8, 24, 70 and 160 μm, mostly from Spitzer, for their sample sources.…”
Section: Total Infrared Bolometric Luminosities and Lfmentioning
confidence: 99%
“…The extrapolation from the mid-infrared (MIR) emission to the total IR emission is known to be quite difficult but, to z = 1, we still observe a wavelength range also observed in the nearby universe by either IRAS or ISO. As a consequence, several calibrations and IR SED templates were proposed in the literature based on observations of nearby galaxies by IRAS and/or ISO (e.g., Chary & Elbaz 2001;Dale & Helou 2002;Takeuchi et al 2005a). The Spitzer observations have illustrated the large variety of IR spectral energy distributions in nearby galaxies (Dale et al 2005;Rieke et al 2008).…”
Section: Estimating the Ir Luminositiesmentioning
confidence: 99%
“…We also consider the calibrations of Takeuchi et al (2005a) (hereafter TBI05) based on a statistical analysis of all the galaxies observed in the four bands of IRAS in the Point Source Catalog (Saunders et al 2000). The relation obtained by TBI05 at λ = 12 μm for local galaxies (i.e., when we observe a galaxy at λ obs , its emitted wavelength λ em corresponds to 12 μm at z = 1) is slightly modified to take into account a slight non-linearity for the most luminous objects,…”
Section: Estimating the Ir Luminositiesmentioning
confidence: 99%